Comparison of surgical conditions during propofol or desflurane anesthesia for endoscopic sinus surgery - Cho, Kwangrae (The Korean Society of Anesthesiologists, 2012)
BACKGROUND: Reduction of intraoperative bleeding is necessary to achieve the ideal surgical field for the endoscopic sinus surgery (ESS). Intraoperative intra nasal bleeding is influenced by various anesthetics. This study compared surgical field condition between propofol/remifentanil (PR) based anesthesia and desflurane/remifentanil (DR) based anesthesia. METHODS: American Society of Anesthesiologists physical status class I or II patients undergoing ESS were randomly assigned to group PR (n = 36) or group DR (n = 32). The extent of the preoperative surgical lesion was classified as high (> 12) and low (≤ 12) Lund-Mackay (LM) scores according to the computed tomography findings. The target mean blood pressure was maintained at 70-80 mmHg. Only one surgeon was involved in rating the visibility of the surgical field on a numeric rating scale (NRS) every 10 minutes. RESULTS: There was a different surgical field grade from PR to DR. The mean (SD) surgical field score of NRS for the PR and DR was 2.3 (0.57) and 2.7 (0.67), respectively (P = 0.006). Especially in the high-LM score patients, the mean (SD) of surgical field score for the PR and DR was 2.4 (0.67) and 3.0 (0.63), respectively (P = 0.012). CONCLUSIONS: In the high-LM score patients, PR based anesthesia resulted in better surgical field condition for ESS than DR based anesthesia. In ESS, PR based anesthesia is considered to be helpful.